Integrated analysis of the whole transcriptome of skeletal muscle reveals the ceRNA regulatory network related to the formation of muscle fibers in Tan sheep - Cui, Ran; Kang, Xiaolong; Liu, Yufang; Liu, Ximing; Chan, Shuheng; Wang, Yubei; Li, Zhen; Ling, Yao; Feng, Dengzhen; Li, Menghua; Lv, Fenghua; Fang, Meiying (Frontiers in Genetics, 2022)
Meat quality is highly influenced by the kind of muscle fiber, and it can be significantly improved by increasing the percentage of slow-twitch fibers. It is still not known which genes control the formation of muscle fibers or how those genes control the process of forming in sheep until now. In this study, we used high-throughput RNA sequencing to assess the expression profiles of coding and noncoding RNAs in muscle tissue of Tan sheep and Dorper sheep. To investigate the molecular processes involved in the formation of muscle fibers, we collected two different muscle tissues, longissimus dorsi and biceps femoris, from Tan sheep and Dorper sheep. The longissimus dorsi of Tan sheep and Dorper sheep displayed significantly differential expression levels for 214 lncRNAs, 25 mRNAs, 4 miRNAs, and 91 circRNAs. Similarly, 172 lncRNAs, 35 mRNAs, 12 miRNAs, and 95 circRNAs were differentially expressed in the biceps femoris of Tan sheep and Dorper sheep according to the expression profiling. GO and KEGG annotation revealed that these differentially expressed genes and noncoding RNAs were related to pathways of the formation of muscle fiber, such as the Ca2+, FoxO, and AMPK signaling pathways. Several key genes are involved in the formation of muscle fibers, including ACACB, ATP6V0A1, ASAH1, EFHB, MYL3, C1QTNF7, SFSWAP, and FBXL5. RT-qPCR verified that the expression patterns of randomly selected differentially expressed transcripts were highly consistent with those obtained by RNA sequencing. A total of 10 lncRNAs, 12 miRNAs, 20 circRNAs, and 19 genes formed lncRNA/circRNA-miRNA-gene networks, indicating that the formation of muscle fiber in Tan sheep is controlled by intricate regulatory networks of coding and noncoding genes. Our findings suggested that specific ceRNA subnetworks, such as circ_0017336-miR-23a-FBXL5, may be critical in the regulation of the development of muscle fibers, offering a valuable resource for future study of the development of muscle fibers in this animal species. The findings increase our understanding of the variety in how muscle fibers originate in various domestic animals and lay the groundwork for future research into new systems that regulate the development of muscle.